miR-27-3p Enhances the Sensitivity of Triple-Negative Breast Cancer Cells to the Antitumor Agent Olaparib by Targeting PSEN-1, the Catalytic Subunit of Γ-Secretase - Zhao, Meng; Sun, Baisheng; Wang, Yan; Qu, Gengbao; Yang, Hua; Wang, Pilin (Frontiers in Oncology, 2021)
Olaparib has been used in the treatment of triple-negative breast cancer (TNBC) with BRCA mutations. In the present study, we demonstrated the effect of miR-27-3p on the γ-secretase pathway by regulating the sensitivity of TNBC cells to olaparib. miR-27-3p, a microRNA with the potential to target PSEN-1, the catalytic subunit of γ-secretase mediating the second step of the cleavage of the Notch protein, was identified by the online tool miRDB and found to inhibit the expression of PSEN-1 by directly targeting the 3'-untranslated region (3'-UTR) of PSEN-1. The overexpression of miR-27-3p inhibited the activation of the Notch pathway via the inhibition of the cleavage of the Notch protein, mediated by γ-secretase, and, in turn, enhanced the sensitivity of TNBC cells to the antitumor agent olaparib. Transfection with PSEN-1 containing mutated targeting sites for miR-27-3p or the expression vector of the Notch protein intracellular domain (NICD) almost completely blocked the effect of miR-27-3p on the Notch pathway or the sensitivity of TNBC cells to olaparib, respectively. Therefore, our results suggest that the miR-27-3p/γ-secretase axis participates in the regulation of TNBC and that the overexpression of miR-27-3p represents a potential approach to enhancing the sensitivity of TNBC to olaparib.